News to me : adventures of an accidental journalist - Hertzel, Laurie (University of Minnesota Press, 2010)
Laurie Hertzel wasn't yet a teenager in Duluth, Minnesota, when she started her first newspaper, which she appropriately christened Newspaper. Complete with the most sensational headlines of the day-MARGO FLUEGEL HAS ANOTHER BIRTHDAY!-and with healthy competition from her little brothers and their rival publication, Magapaper (a magazine and a newspaper), this venture would become Hertzel's first step toward realizing what her heart was already set on: journalism as her future. News to Me is the adventurous story of Hertzel's journey into the bustling world of print journalism in the mid-1970s.